ПЕДАГОГІЧНА КУЛЬТУРА МАЙБУТНЬОГО ВЧИТЕЛЯ, її РОЛЬ У НАВЧАННІ ТА ВИХОВАННІ ОСОБИСТОСТІ ДИТИНИ В ІНТЕГРОВАНОМУ СЕРЕДОВИЩІ (Педагогіка вищої та середньої школи, 2009)
The article is devoted to the research of the importance of pedagogical culture of a future teacher. The pedagogical condition of future teacher's pedagogical culture (integrity , continuity, rystematic character) formation have been dearmined in the article.